Penentuan Azimut Kiblat Masjid Kampus UIN Sultanah Nahrasiyah Lhokseumawe Menggunakan Rumus Segitiga Bola Berbasis Python - Ravik Walhidayah; Ismail Ismail (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
Prayer time is a compulsory act of worship for Muslims, the validity of which depends on the fulfillment of specific conditions, one of which is facing the qibla, the direction of the Kaaba in the Masjid al-Haram, Makkah. Therefore, accurate determination of the qibla direction is a crucial aspect of performing prayer. Various methods have been used to determine the qibla direction, such as the annual Rashdul Qiblah phenomenon and calculations based on spherical trigonometry. The Rashdul Qiblah method is simple and accurate; however, its application is limited to specific times. In contrast, spherical trigonometry can be applied at any time and offers high precision, but the calculation process is relatively complex and prone to human error. This study aims to implement spherical trigonometry using the Python programming language to simplify the process of qibla direction determination and to evaluate its accuracy. The research employs a library research method with a computational simulation approach. The qibla direction is calculated by inputting the latitude and longitude coordinates of the location and the Kaaba into a Python program, and the results are then compared with field measurement data obtained using a theodolite. The results show that the Python-based qibla direction calculation produces an azimuth value with a difference of 32.62 arcseconds compared to the theodolite measurements. This difference is considered very small and does not practically affect the accuracy of the qibla direction. Therefore, the proposed method is proven to be accurate, efficient, and suitable as a modern alternative for determining the qibla direction.